2008
DOI: 10.1021/jm7014815
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel A2B Adenosine Receptor Antagonist as a Clinical Candidate for Chronic Inflammatory Airway Diseases

Abstract: Recently, we have reported a series of new 1,3-symmetrically (R 1 = R 3) substituted xanthines ( 3 and 4) which have high affinity and selectivity for the human adenosine A 2B receptors (hA(2B)-AdoR). Unfortunately, this class of compounds had poor pharmacokinetic properties. This prompted us to investigate the effect of differential alkyl substitution at the N-1 and N-3 positions ( N 1-R not equal to N 3-R) on A(2B)-AdoR affinity and selectivity; we had the dual objectives of enhancing affinity and selectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 31 publications
0
38
0
Order By: Relevance
“…Unfortunately, this class of compounds showed poor pharmacokinetic properties. Further studies about this scaffold, and in particular on the influence of differential alkyl substitution at the N1-and N3-positions on the A 2B affinity and selectivity [38], led to the first A 2B antagonist with a potential significant therapeutic value CVT-6883 (15). CVT-6883 displayed high affinity and selectivity for the A 2B AR relative to the other adenosine subtypes and a good pharmacokinetic profile in rats.…”
Section: Xantinementioning
confidence: 99%
“…Unfortunately, this class of compounds showed poor pharmacokinetic properties. Further studies about this scaffold, and in particular on the influence of differential alkyl substitution at the N1-and N3-positions on the A 2B affinity and selectivity [38], led to the first A 2B antagonist with a potential significant therapeutic value CVT-6883 (15). CVT-6883 displayed high affinity and selectivity for the A 2B AR relative to the other adenosine subtypes and a good pharmacokinetic profile in rats.…”
Section: Xantinementioning
confidence: 99%
“…On the other hand, the blockade of A 2B ARs was also shown to lead to anti-inflammatory effects. Therefore, A 2B -selective antagonists were proposed as a novel approach for the management and treatment of asthma and chronic obstructive pulmonary disease (Kalla et al, 2006Elzein et al, 2008), intestinal inflammation (Kolachala et al, 2008;El-Tayeb et al, 2011), and inflammatory pain (Bilkei-Gorzo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…26 Compound 5 is currently evaluated for cardiopulmonary disease in an ascending-dose phase I clinical study by CV Therapeutics, representing the first A 2B antagonist in clinical trials. 27 Thus, the asthmatic response to adenosine is likely to be mediated via A 2B AdoR, providing a firm basis for the development of A 2B antagonists as new antiasthmatic agents. 28 The A 2B AdoR antagonists 8-(p-bromophenyl)-1-propargylxanthine (PSB-50), 4-(1-butylxanthin-8-yl)benzoic acid (PSB-53), 8-(4-(2-(4-benzylpiperazin-1-yl)-2-oxoethoxy)phenyl)-1-butylxanthine (PSB-55), and PSB-1115 (3) were tested among other subtype-selective AdoR antagonists for their analgesic potency in mice using the hot plate test.…”
Section: Introductionmentioning
confidence: 99%
“…Chart 1. A 2B Antagonists and their K i Values at AdoR Subtypes (h ) Human, r ) Rat) 9,27,[40][41][42][43][44][45][46][47] A recent study showed that A 2B AdoR knockout mice exhibit attenuated tumor growth and decreased levels of vascular endothelial growth factor (VEGF) in the tumors after inoculation with Lewis lung carcinoma when compared to wild-type mice, pointing at the involvement of A 2B AdoR activation in the neovascularization of tumors. The release of VEGF was increased by the nonselective agonist NECA but not by the A 2A -selective AdoR agonist 2-p-(2-carboxyethyl)phenethylamino-5′-N-ethylcarboxamidoadenosine (CGS-21680), whereas a combination of NECA and the selective A 2B AdoR antagonist 5 did not show this effect, indicating that A 2B antagonists might have the potential to inhibit tumor vascularization.…”
Section: Introductionmentioning
confidence: 99%